The policy operations room: Analyzing path-dependent decision-making in wicked socio-ecological disruptions. (February 2022) - Hukkinen, Janne I.; Eronen, Jussi T.; Janasik, Nina; Kuikka, Sakari; Lehikoinen, Annukka; Lund, Peter D.; Räisänen, Helmi; Virtanen, Mikko J.
Highlights: Develops a new framework for practice and analysis of strategic crisis management. Permits consideration of long-term implications of urgent decisions. Enhances expert input to management of chronic socio-ecological disruptions. Abstract: The magnitude and speed of change in complex human-environmental systems pose a systemic dilemma for societies. Human-induced environmental changes have pushed Earth's socio-ecological systems into an era of chronic, complex, and rapid disruptions, which call for quick intuitive decisions and effective implementation. Yet the complexity, interconnectedness and long lead times of the problems would require thoughtful and time-consuming weighing of evidence by a broad range of experts. To address the dilemma, we develop a framework, the Policy Operations Room (POR), for simultaneous practice and analysis of decision-making that prevents decisions made under time pressure from leading to unwanted socio-ecological disruptions decades ahead. The POR framework is based on earlier research on control rooms of critical infrastructures and simulation exercises of emergency response, and preliminary data from our first experiments with PORs. It immerses the policymakers in a simulated "time machine" that combines the real-time reliability management of control rooms with the long-term planning for crisis avoidance and preparedness. The POR framework can contribute significantly to novel styles of decision-making by policymakers, engineers, and corporate strategists responsible for developing urgent, forward-looking, and evidence-based policies to cope with the coming challenges of human-environmental interaction.